Carbon Dots for Intracellular Sensing. Issue 9 (15th June 2022) - Lin, Fengming; Jia, Chenyang; Wu, Fu-Gen
Abstract : Carbon dots (CDs), a type of small, carbon element‐based nanomaterials, have found numerous applications in many fields due to their outstanding properties like fascinating photoluminescence characteristic, great biocompatibility, easy and economical synthesis, and facile functionalization. Over the last decade, huge progress and achievements have been made in terms of the applications of CDs in cellular detection. However, a comprehensive review focusing on this topic is still lacking. Herein, the recent progress in CDs‐mediated intracellular detection, including the fluorescence imaging of cellular structures (e.g., nucleus/nucleolus, mitochondrion, lysosome, endoplasmic reticulum, Golgi apparatus, and lipid droplet), the fluorescence detection of a large variety of cellular substances (including endogenous biomacromolecules and their monomers, vitamins, important metabolites, adenosine triphosphate, reactive oxygen species, biothiols, ions, and exogenous compounds), and the monitoring of cellular parameters (pH, temperature, and mitochondrial membrane potential), is thoroughly reviewed. The synthesis, functionalization, and performance of the CDs that serve as fluorescent nanoprobes in living cells are presented. Their underlying working mechanisms are also discussed if available. Finally, the challenges and future research directions of the related research field are listed. This review may foster the future development of more CDs with better cellular sensing performance. Abstract : A comprehensive review on the advancements in the carbon dot‐based intracellular detection (including imaging of cellular structures, detection of cellular substances, and monitoring of cellular parameters) is given. The current limitations and future research directions in this field are also proposed.